2021
DOI: 10.4252/wjsc.v13.i12.1928
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin a alleviates oxidative stress-induced senescence in nucleus pulposus-derived mesenchymal stem cells through SIRT1/PGC-1α pathway

Abstract: BACKGROUND In degenerative intervertebral disc (IVD), an unfavorable IVD environment leads to increased senescence of nucleus pulposus (NP)-derived mesenchymal stem cells (NPMSCs) and the inability to complete the differentiation from NPMSCs to NP cells, leading to further aggravation of IVD degeneration (IDD). Urolithin A (UA) has been proven to have obvious effects in delaying cell senescence and resisting oxidative stress. AIM To explore whether UA can alleviate NPMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
5
22
0
Order By: Relevance
“…The results showed that 1,25(OH) 2 D 3 showed no cytotoxic effect on cell viability at a concentration of 10 −8 M to 10 −12 M for the different exposure times (0, 12, 24, and 48 h) ( Figure 2(a) ); 10 −10 M of 1,25(OH) 2 D 3 was chosen for the subsequent experiments. Additionally, cell proliferation was appropriately inhibited when treated with 100 μ M H 2 O 2 for 6 h, which was the same result as our previous study [ 24 , 33 ] ( Figure 2(b) ). Therefore, this condition was used to induce oxidative stress damage in NPMSCs in the following experiments.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that 1,25(OH) 2 D 3 showed no cytotoxic effect on cell viability at a concentration of 10 −8 M to 10 −12 M for the different exposure times (0, 12, 24, and 48 h) ( Figure 2(a) ); 10 −10 M of 1,25(OH) 2 D 3 was chosen for the subsequent experiments. Additionally, cell proliferation was appropriately inhibited when treated with 100 μ M H 2 O 2 for 6 h, which was the same result as our previous study [ 24 , 33 ] ( Figure 2(b) ). Therefore, this condition was used to induce oxidative stress damage in NPMSCs in the following experiments.…”
Section: Resultssupporting
confidence: 90%
“…The separated NPMSCs gathered into a chrysanthemum shape and formed into a long spindle shape after passage ( Figure 1(a) ). Similar to our previous studies [ 18 , 23 , 33 ], the MSC-associated surface markers CD73, CD90, and CD105 in NPMSCs presented high fluorescence expression, whereas the surface markers CD34 and CD45 showed presented low fluorescence expression ( Figure 1(b) ). The results of osteogenic, adipogenic, and chondrogenic induction in vitro confirmed the multipotential differentiation of NPMSCs ( Figure 1(c) ).…”
Section: Resultssupporting
confidence: 90%
“…The cells were spindle-shaped after passage (Figure 2(A)). Similar to our previous studies [11,31], NPMSC can induce osteogenesis, chondrogenesis and adipogenic differentiation in vitro (Figure 2(B)), so its multilineage differentiation ability has been con rmed. In addition, the related antigens CD105 97.5±0.12 , CD90 98.9±0.06 and CD73 98.7±0.13 marked on the surface of MSC were highly expressed in NPMSC, while CD45 0.83±0.07 and CD11b/c 2.45±0.09 were lowly expressed(Figure 2(C)).…”
Section: Identi Cation Of Npmscssupporting
confidence: 88%
“…Orthopedics had the most highly cited papers ( n = 2), followed by Research Experimental Medicine, Pharmacology Pharmacy, and Rheumatology. In addition, National Natural Science Foundation of China had the most records ( n = 143), the highest H-index of 30, the highest total citations ( n = 2,852) and average citations ( n = 19.94) ( Shi et al, 2021 ). National Institutes of Health was the second with records ( n = 27), H-index of 16, the total citations ( n = 1,044) and average citations ( n = 38.67).…”
Section: Resultsmentioning
confidence: 99%
“…Cell senescence in IDD results from the general aging process and the structure and tissue specificity of discs ( Zhang et al, 2020 ). A recent study proved that Urolithin A could activate the SIRT1/PGC-1α signaling pathway to protect mitochondrial function and alleviate cell senescence and IDD in vivo and vitro ( Shi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%